The diagnostic yield and complications of open lung biopsies in kidney transplant patients with pulmonary disease - Tomotani, Daniere Yurie Vieira; Bafi, Antônio Tonete; Pacheco, Eduardo Souza; de Sandes-Freitas, Tainá Veras; Viana, Laila Almeida; de Oliveira Pontes, Edgar Porto; Tamura, Nikkei; Tedesco-Silva Jr, Hélio; Machado, Flavia Ribeiro; Freitas, Flávio Geraldo Rezende (Journal of Thoracic Disease, 2017)
Background: The purpose of this study was to assess the efficacy of open lung biopsy (OLB) in determining the specific diagnosis and the related complications in patients with undiagnosed diffuse pulmonary infiltrates. Methods: This single center, retrospective study included adult kidney transplant patients who underwent OLB. The patients had diffuse pulmonary infiltrates without definitive diagnoses and failed to respond to empiric antibiotic treatment. We analyzed the number of specific diagnoses, changes in treatment and the occurrence of complications in these patients. A logistic regression was used to determine which variables were predictors of hospital mortality. Results: From April 2010 to April 2014, 87 patients consecutively underwent OLB. A specific diagnosis was reached in 74 (85.1%) patients. In 46 patients (53%), their therapeutic management was changed after the OLB results. Twenty-five (28.7%) patients had complications related to the OLB. The hospital mortality rate was 25.2%. Age, SAPS3 score and complications related to the procedure were independent predictors of all-cause mortality. Conclusions: OLB is a high-risk procedure with a high diagnostic yield in kidney transplant patients with diffuse pulmonary infiltrates who did not have a definitive diagnosis and who failed to respond to empiric antibiotic treatment. Complications related to OLB were common and were independently associated with intra-hospital mortality.